Evolutionary intelligence in agent modeling and interoperability - Miranda, Miguel (2011)
A healthcare organization to be tuned with the users expectations, and to act ac- cording to its goals, must be accountable for the quality, cost, and overall care of the beneficiaries. In this paper we describe a model of clinical information designed to make health information systems properly interoperable and safely computable, based on an Evolutionary Intelligence approach that generates quantified scenarios from defective knowledge. The model is a response to a number of requirements, ranging from the semantic ones to the evaluation of software performance at run- time; it is among the biggest challenges in engineering nowadays.